Characterization and Classification of Rice and Associated Non-rice Soils of Assam - Samiron Dutta; Marami Dutta, Shraddha Mohanty*, R.M. Karmakar (Journal of the Indian Society of Soil Science, 2019)
Eight soil profiles, four each from mono-cropped rice (P1, P2, P3 and P4) and associated non-rice (NP1, NP2, NP3 and NP4) areas collected from Jorhat, Golaghat, Sivasagar and Dibrugarh districts, respectively in the Upper Brahmaputra valley of Assam were studied for pedogenic characterization. Several variations were observed in morphological, physical and chemical characteristics among rice and associated non-rice soils. Soil colour varied from dark gray (10YR 4/1) to brownish yellow (10YR 6/8) having dominant hue of 10YR and value ranging from 4 to 7 and chroma from 1 to 8. Yellow (10YR 6/8) to light red (2.5YR 6/8) mottles were observed in all horizons both in rice and non-rice profiles except the upper four horizons of NP4. The soil textural class varied from sandy clay loam to clay. Rice soils were dominantly clay loam to clay in texture while non-rice soils were relatively sandy clay loam to silty clay loam. The structures of soils were massive in surface horizons of rice soils and varied from weak to strong, fine to coarse and angular to subangular blocky in the sub-surface horizon of both rice and non-rice soils. Thin clay cutans were observed in sub-surface horizons of all profiles except NP4 while few to abundant Fe-Mn glaebules were found in sub-surface horizons except in NP3 and NP4. Sand, silt and clay contents varied from 11.3-49.0, 21.5-50.8 and 26.2-56.9% in rice and 23.3-65.4, 11.4-42.9 and 14.4-44.4% in non-rice soils, respectively. Organic carbon content in soil varied from 2.0-12.0 and 0.5-10.0 g kg-1 in rice and non-rice soils, respectively. Bulk density of soils increased with soil depth, Soil pH varied from 4.4-6.0 and EC was found to be low (0.11-0.20 dS m-1). The CEC of soils varied from 7.5-14.1 cmol(p+)kg-1 in rice and 5.1-12.7 cmol(p+)kg-1 in non-rice soils having dominance of exch. Ca2+ followed by Mg2+, Na+ and K+. The amount of exchange acidity ranged from 0.29-2.02 cmol(p+)kg-1 in rice soils and from 0.18-1.49 cmol(p+)kg-1 in non-rice soils. Base saturation of soils was low (32.3-57.5%). Soils were classified as Typic Epiaqualfs (P1), Aeric Epiaqualfs (NP1, P2, P3, NP3 and P4), Ultic Hapludalfs (NP2) and Typic Dystrudepts (NP4) at sub-group level.